The isoflavone daidzein directly affects porcine ovarian cell functions and modifies the effect of follicle‐stimulating hormone. Issue 1 (27th April 2016) - Sirotkin, A. V.; Alexa, R.; Kádasi, A.; Štochmaľová, A.; Morovič, M.; Laurinčik, J.; Harrath, A. H.; Grossmann, R.
Summary: The key biological active molecule of soya is the isoflavone daidzein, which possesses phytoestrogenic activity. The direct effect of soya and daidzein on ovarian cell functions is not known. This study examined the effect of daidzein on basic porcine ovarian granulosa cell functions and the response to follicle‐stimulating hormone (FSH). We studied the effects of daidzein (0, 1, 10 and 100  μ m ), FSH (0, 0.01, 0.1, 1 IU/ml) and combinations of FSH (0, 0.01, 0.1, 1 IU/ml) + daidzein (50  μ m ) on proliferation, apoptosis and hormone release from cultured porcine ovarian granulosa cells and ovarian follicles. The expression of a proliferation‐related peptide (PCNA) and an apoptosis‐related peptide (Bax) was analysed using immunocytochemistry. The release of progesterone (P4) and testosterone (T) was detected using EIA. Leptin output was analysed using RIA. Daidzein administration increased granulosa cell proliferation, apoptosis and T and leptin release but inhibited P4 output. Daidzein also increased T release and decreased P4 release from cultured ovarian follicles. Follicle‐stimulating hormone stimulated granulosa cell proliferation, apoptosis and P4, T and leptin release. The addition of daidzein promoted FSH‐stimulated apoptosis (but not proliferation) but suppressed FSH‐stimulated P4, T and leptin release. Our observations of FSH action confirm previous data on the stimulatory effect of FSH on ovarian cell proliferation, apoptosis and steroidogenesis and demonstrate for the first time the involvement of FSH in the upregulation of ovarian leptin release. Our observations of daidzein effects demonstrated for the first time that this soya isoflavone affected basic ovarian cell functions (proliferation, apoptosis and hormones release) and modified the effects of FSH. Daidzein promoted FSH action on ovarian cell proliferation and apoptosis and suppressed, and even inverted, FSH action on hormone release. The direct action of daidzein on basic ovarian cell functions and the ability of these cells to respond to FSH indicate the potential influence of soya‐containing diets on female reproductive processes via direct action on the ovary.